The Prevalence of Integument Injuries and Associated Risk Factors Among Canadian Turkeys - Leishman, Emily M.; van Staaveren, Nienke; Osborne, Vern R.; Wood, Benjamin J.; Baes, Christine F.; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2022)
Injurious pecking can cause a wide range of damage and is an important welfare and economic issue in turkey production. Aggressive pecking typically targets the head/neck (HN) area, and feather pecking typically targets the back/tail (BT) area; injuries in these separate areas could be used as a proxy for the level of aggressive and feather pecking in a flock. The objective of this study was to identify risk factors for integument injuries in Canadian turkey flocks. A survey containing a questionnaire about housing and management practices and a scoring guide was distributed to 500 turkey farmers across Canada. The farmer scored pecking injuries in two different body areas (HN and BT) on a 0-2 scale on a subset of birds within each flock. Multivariable logistic regression modelling was used to identify factors associated with the presence of HN and BT injuries. The prevalence of birds with integument injuries ranged widely between the flock subsets (HN=0-40%, BT=0-97%), however the mean prevalence was low (HN=6%, BT=10%). The presence of injuries for logistic regression was defined as flocks with an injury prevalence greater than the median level of injury prevalence (3.3% HN and 6.6% BT). The final logistic regression model for HN injuries contained five variables: flock sex, flock age, number of daily inspections, number of different people during inspections, and picking up birds during inspections (N=62, pR2=0.23, α=0.05). The final logistic regression model for BT injuries contained six variables: flock sex, flock age, litter depth, litter condition, inspection duration, and use of hospital pens for sick/injured birds (N=59, pR2=0.29, α=0.05). Flock age, and to a lesser extent, sex was associated with both types of injuries. From a management perspective, aggressive pecking injuries appear to be influenced by variables related to human interaction, namely during inspections. On the other hand, the presence of feather pecking injuries, was associated with litter condition and other management factors like separating sick birds. Future research on injurious pecking in turkeys should focus on these aspects of housing and management to better describe the relationship between the identified variables and the prevalence and severity of these conditions.